Serum Interleukin-6 Levels are Positively Correlated with the Severity of Acne Vulgaris - Triatmakusuma, Yogi; Praharsini, I Gusti Ayu Agung; Darmaputra, I Gusti Nyoman; Winaya, Ketut Kwartantaya; Karna, Ni Luh Putu Ratih Vibriyanti; Puspawati, Ni Made Dwi (Newinera Publisher, 2024)
Acne vulgaris is a chronic inflammatory disease that affects the pilosebaceous unit. This disease occurs on the skin of the face, body, back, and other areas of the body, and can leave scars on the skin which can be temporary or permanent. Recent data shows that the inflammatory process is the initial process in the pathogenesis of acne, several pro-inflammatory cytokines, one of which is interleukin 6 (IL-6), which plays a role in acne vulgaris. Analytical observational study with a cross-sectional approach. The research was carried out from February - November 2023 at the Skin and Venereology Polyclinic, RSUP Prof. Dr. I.G.N.G. Ngoerah Denpasar and the Clinical Pathology Laboratory of Prof IGNG Ngoerah Hospital. The sample consisted of 47 samples of patients with acne and 20 samples without acne aged 8 - 45 years who were selected through consecutive sampling according to inclusion and exclusion criteria. A sample of 3 milliliters of venous blood is taken which will then be checked for IL-6 with an ELISA kit. Data analysis with SPSS version 24 and p value <0.05 is significant. The mean IL-6 serum levels in the acne group was 110.2 ± 88.3 pg/ml while in the non-acne group it was 26.7 ± 23.7 pg/ml. There was a significant difference in the category of IL-6 levels in the acne and non-acne groups (95% CI 55.1 - 155.3, p<0.001). The correlation analysis of IL-6 levels with the severity of acne was strongly positive (r=0.951, p<0.001).